(untitled) (Jahangirnagar University Journal of Biological Sciences, 2022)
Mucor circinelloides were isolated from post harvest infected papaya, which was collected from Savar region. M. circinelloides was identified by morphology and biology of fungus based on colony features, fungal mycelium, sporangia and sporagiospores as well as molecular approach. Mycelial colonies are floccose, pale greyish-brown. Sporangiophores were transparent, long, erect and shorter branches, 4.5-7 x 3.5-5 μm in size. Sporangia are hyaline, spherical, ranged from 20-80 μm in diameter. Columellae were hyaline, spherical to ellipsoidal up to 50 μm in diameter. The highest mycelial growth was recorded in potato dextrose agar (PDA) medium for the growth and development of M. circinelloides. Temperature 30°C was optimum. This fungus grew well in pH 7. So, tested fungi grew well in neutral condition. Complete dark condition was favourable for the vegetative growth of the fungus. The molecular phylogeny in morphologically identified post-harvest pathogenic fungi of papaya such as M. circinelloides were studied based on their ITS. The sequences of ITS region of M. circinelloides revealed that the total length was 620 bp and sequence analysis suggested that 5.8S of rDNA sequences were identical. Jahangirnagar University J. Biol. Sci. 10(1 & 2): 31-38, 2021 (June & December)